Hybrid Modulation Scheme for Switching Loss Reduction in a Modular Multilevel High-Voltage Direct Current Converter - Kim, Seok Min; Jeong, Min Gyo; Kim, Juyong; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2019)
A modular multilevel converter (MMC) is regarded as a promising topology in high-voltage direct current systems. However, the MMC consists of numerous submodules (SMs) and switching devices, which lead to a considerable switching loss, and increased cost and size of the heat sink. To mitigate these issues, this paper presents a novel modulation method composed of fundamental frequency modulation (FFM) and multicarrier-based sinusoidal pulsewidth modulation schemes. The main purpose of this modulation method is the reduction of switching loss while maintaining good harmonic performance. However, the FFM scheme leads to the unbalanced capacitor voltage of each SM in the MMC. Accordingly, this paper additionally proposes the rotation method and selective voltage balancing control for SMs to ensure effective performance of the method. Simulation and experimental results verify the effectiveness and performance of the proposed modulation scheme through switching loss and spectral analyses.
Keywords: Direct current transmissions; Hybrid modulation; Modular multilevel converters; Multicell; Switching loss; Direct current transmission; hybrid modulation; modular multilevel converter; multicell topology; switching loss